2020
DOI: 10.1101/2020.09.25.311993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant Prionome maps reveal specific roles of prion-like proteins in stress and memory

Abstract: Prions can be considered as molecular memory devices, generating reproducible memory of a conformational change. Prion-like proteins (PrLPs) have been demonstrated to be present in plants, but their role in plant stress and memory remains largely unexplored. In this work, we report the widespread presence of PrLPs in plants through a comprehensive analysis of 39 genomes representing major taxonomic groups. We find diverse functional roles associated with plant prionomes. Investigation of the rice transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Since the original characterization of prion domains in yeast (Chernoff et al, 1995;Serio et al, 1999), PrLDs with similar features have been identified and studied in other organisms such as viruses (Tetz and Tetz, 2018), bacteria (Iglesias et al, 2015;Yuan and Hochschild, 2017;Choi et al, 2022), protozoan (Pallares et al, 2018) or humans (An and Harrison, 2016;Iglesias et al, 2019). Plants have received less attention, with only a few studies focusing on PrLDs' coverage and function (Chakrabortee et al, 2016;Dorone et al, 2021;Garai et al, 2021). To identify the potential presence of CARs in PrLDs (pCARs) from plants, the proteomes of five different model higher plants were first screened with the PLAAC algorithm.…”
Section: Prevalence Of Pcars In Plant Prldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the original characterization of prion domains in yeast (Chernoff et al, 1995;Serio et al, 1999), PrLDs with similar features have been identified and studied in other organisms such as viruses (Tetz and Tetz, 2018), bacteria (Iglesias et al, 2015;Yuan and Hochschild, 2017;Choi et al, 2022), protozoan (Pallares et al, 2018) or humans (An and Harrison, 2016;Iglesias et al, 2019). Plants have received less attention, with only a few studies focusing on PrLDs' coverage and function (Chakrabortee et al, 2016;Dorone et al, 2021;Garai et al, 2021). To identify the potential presence of CARs in PrLDs (pCARs) from plants, the proteomes of five different model higher plants were first screened with the PLAAC algorithm.…”
Section: Prevalence Of Pcars In Plant Prldsmentioning
confidence: 99%
“…An opposite tendency is observed for interpCARs, which seem to compensate the sequential amyloidogenic load by reducing the aromatics and increasing b-breakers. (Garai et al, 2021) proteins from plants. The fact that a significant proportion of PrLDs is pCAR-positive makes it challenging to disentangle the contributions of the complete PrLD sequence and pCARs only in a given protein to the detected enrichments.…”
Section: Functional Enrichments Of Pcars In a Thalianamentioning
confidence: 99%
“…Prion-like domains (PLDs) are typically characterized by their low complexity sequence features with an overrepresentation of aromatic (Y/F) and polar amino acids (G/S/Q/N) and depletion of charged residues 6,7 . Proteins with PLDs have been identified in all life forms [8][9][10][11][12] . Prion proteins were initially discovered as proteinaceous infectious agents in bovine spongiform encephalopathy and other neurodegenerative diseases 4, [13][14][15] , but are increasingly recognized with key functional roles in driving phase separation of RNA-binding proteins in the cell, and in the formation of functional amyloids 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…CK extends thanks to Ashwani Pareek, Stress Physiology and Molecular Biology Laboratory, School of Life Sciences, JNU, for hosting her during the DST-INSPIRE fellowship. A version of this article is available online as a preprint in bioRxiv ( Garai et al, 2020 ).…”
mentioning
confidence: 99%